A modified spatial smoothing-based Nystrom approach for coherent target in bistatic MIMO radar. Issue 9 (1st September 2020) - Baidoo, Evans; Hu, Jurong; Zhan, Lei
ABSTRACT: The performance of most angle estimation system degrades when the signal attributes coherency coupled with the high computational burden of the preprocessing technique. This paper addresses the issue of the computational burden of the coherent angle estimation for the bistatic multiple-input multiple-output (MIMO) radar. A modified spatial smoothing technique is initially developed by ensuring the generation of a lower rank kernel matrix of the decorrelated signal via a Nyström approach. Then the formed data matrix is subjected to the shift-invariance technique where the automatic pairing of the angles is estimated without loss of the virtual aperture. Hence, in addition to significantly reducing the computational complexity, the proposed method presents an improved performance against existing techniques verifiable by simulation results.